Mein Kampf : My Struggle - Hitler, Adolf, 1889-1945 (New Dilhi Adarsh Books, 2002)
Although this monumental book was first ignored, it was a significant warning to the world for it contained an outline of Hitler's plans for his rise to power.
Include Index
Keywords: Germany -- Politics and government -- Nationalsozialistische Deutsche Arbeiter-Partei -- Hitler, Adolf, 1889-1945 -- National socialism